1981
DOI: 10.1111/j.2044-8279.1981.tb02480.x
|View full text |Cite
|
Sign up to set email alerts
|

Australian and Filipino Investigations of the Internal Structure of Biggs' New Study Process Questionnaire

Abstract: Summary. The internal structure of the new Study Process Questionnaire (Biggs, 1979) was investigated with samples of 255 Australian and 173 Filipino university students. The internal consistency reliabilities, item and subscale factor analyses were quite favourable for the Australian sample, supporting Biggs' model of the study process complex. However, the low to moderate reliabilities and failure of factor analysis to support Biggs' model indicates that the SPQ may not be suitable for Filipino students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
26
1

Year Published

1990
1990
2016
2016

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 4 publications
6
26
1
Order By: Relevance
“…The early study by Hattie and Watkins (1981) found evidence for six factors underlying the 42 constituent items and for three factors underlying the six subscales of the SPQ, but their report did not present the extracted solutions. In subsequent factor analyses of scores on the subscales, Biggs himself has consistently failed to retrieve the intended factor structure even in the case of Australian students, and has found instead merely a generalised surface approach and a generalised deep approach to studying.…”
Section: Research Outside Australiamentioning
confidence: 92%
See 1 more Smart Citation
“…The early study by Hattie and Watkins (1981) found evidence for six factors underlying the 42 constituent items and for three factors underlying the six subscales of the SPQ, but their report did not present the extracted solutions. In subsequent factor analyses of scores on the subscales, Biggs himself has consistently failed to retrieve the intended factor structure even in the case of Australian students, and has found instead merely a generalised surface approach and a generalised deep approach to studying.…”
Section: Research Outside Australiamentioning
confidence: 92%
“…Hattie and Watkins (1981) administered this 42-item SPQ to 255 Australian university students and found that the internal consistency of each of the six subscales was wholly satisfactory. An analysis of the students' responses to the individual items produced a six-factor solution in which the subscales outlined by Biggs were said to have been 'clearly evident ' (p. 243), and a further analysis of the students' scores on the subscales themselves generated three factors that could be identified with the three major approaches to studying.…”
Section: Research In Australiamentioning
confidence: 99%
“…The factor structure of the Study Process Questionnaire has been investigated in a number of cultures. Studies in Australian (Hattie and Watkins 1981;Biggs 1987), the United Kingdom (O'Neill and Child 1984), and Hong Kong (Biggs and Watkins 1990) have generally supported the factorial validity of the SPQ. However, a Filipino study found a rather different factor structure (Hattie and Watkins 1981).…”
Section: The Cross-cultural Perspectivementioning
confidence: 99%
“…Studies in Australian (Hattie and Watkins 1981;Biggs 1987), the United Kingdom (O'Neill and Child 1984), and Hong Kong (Biggs and Watkins 1990) have generally supported the factorial validity of the SPQ. However, a Filipino study found a rather different factor structure (Hattie and Watkins 1981). That this may be more a problem with the English wording of the SPQ for Filipinos is suggested from the finding that two other learning process questionnaires, based on similar concepts to the SPQ, were found to be factorially valid for Filipinos (Hattie and Watkins 1981;Watkins Hattie, andAstiUa 1986).A previous study (Watkins and Regmi 1990) has also found a meaningful factor structure in Nepalese student responses to one of these questionnaires, the Approaches to Studying Inventory (Entwistle and Ramsden 1983).…”
Section: The Cross-cultural Perspectivementioning
confidence: 99%
“…Biggs (1987) reports Cronbach alpha reliability coefficients for the subscales ranging from 0.61 to 0.77 and the approaches ranging from 0.73 to 0.81. Studies indicating construct validity of the SPQ are reviewed in Biggs (1987Biggs ( , 1988a while the Hattie and Watkins' (1981) investigation independently '...supported the validity of Biggs' subscales' (p. 234).…”
Section: Information Collectedmentioning
confidence: 99%